Persepsi Masyarakat Terhadap Eksistensi Musik Yangere di Desa Tobaol Kecamatan Ibu Kabupaten Halmahera Barat - Baluari, Susanti; Matitaputty, Jenny Koce; Pusparani, Rina (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
The problem in this research is how is the history and the existence of the music of yangere in tobaol village? What is the Tobaol community’s perception of yangere’s music? And what values are contained in yanger music?. The method used in this research is qualitative method. The sampling technique used is purposive sampling. The process of collecting data trough observation, interviews and document studies. Data analysis techniques use 4 important components, namely data collection, data presentation and conclusions or verification. The development of traditional music from the past until now is certainly very different because of the times so that the younger generation prefers modern music compared to traditional music. But until now this music is still maintained and preserved to the next generation. Tobaol poeple’s perception of yangere music in every circle has their own views. The values contained in yangere music are 1)the value of beauty, 2)the value of brotherhood, 3)the value of harmonization dan 4) the value religious.